Wirbelsäulenprobleme beim jungen Athleten - Studer, K.; Camathias, C. (2023)
Abstract:Participation in physical activity has increased in intensity at a young age. Due to their growth with hormonal changes and influences, young people are prone to spinal problems. It is therefore of great importance that trainers, paediatricians and parents are familiar with the sport-specific movement sequences and take measures to prevent potential problems. By understanding the connections, preventive measures can be taken to reduce injuries and overloading of young people. This article provides an overview of common spinal problems in adolescence.